"Illusory" fighting against illiteracy among adults in India - the educational policy - Beata Pietkiewicz-Pareek (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The main objective of presented research is to show the educational policy in India after 1947. The goal of the Adult Education, in collectivistic cultures such as India, is to establish a fully literate society through improved quality and standard of Adult Education and Literacy; to creating citizens who are able to make educated and well informed decisions about their lives and for their families. This is crucial for everything from fostering healthy families to making political decisions, such as who to vote for.